Airbnb, hotels, and localized competition - Maximilian Schaefer; Kevin Ducbao Tran (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The rise of online platforms has disrupted numerous traditional industries. A prime example is the short-term accommodation platform Airbnb and how it affects the hotel industry. On the one hand, consumers can profit from Airbnb due to an increased number of choices and lower prices. On the other hand, critics of the platform argue that it allows professional hosts to operate de facto hotels while being subject to much laxer regulation. Understanding the nature of competition between Airbnb and hotels as well as quantifying consumer welfare gains from Airbnb is important to inform the debate on necessary platform regulation. In this paper, we analyze competition between hotels and Airbnb listings as well as the effect of Airbnb on consumer welfare. For this purpose, we use granular daily-level data from Paris for the year 2017. We estimate a nested logit model of demand that allows for consumer segmentation along accommodation types and the different districts within the city. We extend prior research by accounting for the localized nature of competition within districts of the city. Our results suggest that demand is segmented by district as well as accommodation type. Based on the parameter estimates, we calibrate a supply-side model to assess how Airbnb affects hotel revenues and consumer welfare. Our simulations imply that Airbnb increases average consumer surplus by 4.3 million euro per night and reduces average hotel revenues by 1.8 million euro. Furthermore, we find that 28 percent of Airbnb travelers would choose hotels if Airbnb did not exist.
Keywords: D4; D6; L1; Z38; 330; hotel industry; short-term rentals; localized competition; consumer welfare; sharing economy; peer-to-peer markets; Airbnb